If it's not what You are looking for type in the equation solver your own equation and let us solve it.
72x+436=-96x=
We move all terms to the left:
72x+436-(-96x)=0
We get rid of parentheses
72x+96x+436=0
We add all the numbers together, and all the variables
168x+436=0
We move all terms containing x to the left, all other terms to the right
168x=-436
x=-436/168
x=-2+25/42
| -7m+3m=36 | | 5(x-4)+3=3x+1 | | M-2n=13 | | -x/2+4×2=12×2 | | 81n+4=85 | | -33=0.6k | | x+(-0,5)+1=0 | | 8d+24=32 | | -5p+35=10 | | f/9-25=-27 | | X²-25x+156=0 | | 5(1c+4/5+6=50 | | g/6+17=26 | | 6=8(1s-3/4)-20 | | 4x=2x+83 | | 3+5/5-5x-7/6=x-2/3 | | 0.9(x+100)+0.5x=139 | | 5^2x-7^x-35*5^2x+35*7^x=0 | | 1/2x+200=6540 | | 8x+26.2=1.6 | | F(7)=0.5x | | 5x-6=3x-8= | | -3x×40=10 | | 4i-3=7 | | 2(x=3)=x=9 | | 3/4x+7=25 | | 2(x-6)=6(x+3) | | 9-19=2x+5 | | (3z-5)(3-z)=0 | | A(n)=-11+(n–1)(2) | | -0.75p^2-19p-196=0 | | y/6=-11 |